The absolutely true diary of a part-time Indian - Alexie, Sherman, 1966- (Little, Brown, 2007)
Budding cartoonist Junior leaves his troubled school on the Spokane Indian Reservation to attend an all-white farm town school where the only other Indian is the school mascot.